British soccer academy personnel perceive psychological and technical/tactical attributes as the most important contributors to development - Kite, R. J.; Noon, M. R.; Morris, R.; Mundy, P.; Clarke, N. D. (Journal of Science in Sport and Exercise, 2022)
Purpose: Understanding the desired attributes for talented soccer players may give insight into the process of (de)selection and player development. This study aimed to explore soccer academy personnel`s perceptions of attributes associated with talent and development. Methods: Thirty English and Scottish academy personnel (managers, coaches, recruitment, sports scientists) provided perceptions into what attributes contribute to `talent`, via an online survey. Utilising an E-Delphi method, seven experts refined these inputs over several rounds until a consensus was reached, resulting in 82 agreed terminology. This terminology was resubmitted via a second online survey, where 45 academy personnel rated each using a Likert scale. Results: A ranking of attributes by importance was produced, finding Psychological and Technical/Tactical attributes considered of greatest importance. Differences were observed, whereby recruitment personnel consistently over-emphasised the importance of several attributes compared to other personnel (P = 0.02-0.04). When analyzed within each age phase, 11 variations in the perceived importance of attributes were demonstrated in the youth phase (11-16 years, P = 0.01) compared with 5 in the professional phases (17-23 years, P = 0.01-0.05) Conclusion: The present study demonstrates that `talent` requires multifaceted developments, with academy personnel perceiving psychological attributes the most important contributor to development